Association of Platelet-Monocyte Ratio with Dyslipidemia in Saudi Arabia: A Large, Population-Based Study - Mohammad A. Alfhili; Ghada A. Alotaibi; Mohammed Alfaifi; Yousef Almoghrabi; Jawaher Alsughayyir (Life, 2023)
Background: Abnormal lipid metabolism predisposes to cardiovascular disease. However, dyslipidemia is often asymptomatic leading to its underdiagnosis. Therefore, it is of utmost importance to identify biomarkers that reflect an abnormal lipid profile and trigger the specific investigation of lipid metabolism. The platelet–monocyte ratio (PMR) is a severely understudied index whose association with disturbed lipid markers remains unknown. Methods: A cross-sectional study of the association between PMR and comprehensive lipid profile including total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides (TG), TC/HDL, LDL/HDL, and TG/HDL in 14,269 Saudi subjects was designed. Prevalence, risk measures, association, and the diagnostic performance (i.e., area under the curve (AUC)) were evaluated. Results: Median PMR was significantly elevated in subjects with high TC (p < 0.01), TG, TC/HDL, LDL/HDL, TG/HDL, and LDL and reduced in those with low HDL (all p < 0.0001) compared to normal subjects. The increase in PMR was abolished when only males with high TC were considered. Except for TC and LDL, all other abnormal markers were significantly more prevalent when PMR was lower (higher for HDL) than a certain cutoff specific for each parameter. Moreover, the odds of having PMR readings above or below the selected cutoffs are significantly higher with all lipid abnormalities. PMR was also weakly but significantly and differentially correlated with all forms of dyslipidemia (p < 0.0001). Notably, the highest diagnostic accuracy of PMR was observed for reduced HDL (AUC = 0.608, p < 0.0001) and elevated TG/HDL (AUC = 0.596, p < 0.0001). Conclusions: PMR is a novel, inexpensive, and readily available index that is associated with all forms of dyslipidemia, suggesting its potential use in related disorders.